Handelsgerichtsbarkeit Zur Entstehung des Fachrichtertums zwischen Laienexpertise, Verfahrensförmlichkeit und staatlichem Verfahrensmonopol und ihr Einfluss auf die moderne KfH - Jacob, Sebastian (Schriften zum Prozess- und Verfahrensrecht, 2021)
To this day, German commercial jurisdiction is characterized by the participation of expert lay judges. The work first shows in detail the historical roots and the development of the commercial judges in Italy, in France and in the German legal circles. In particular, the history of the so-called German system is discussed. Subsequently, the author analyzes the essential features of the modern KfH. In a third step, the historical findings are used as possible solutions for current reform efforts concerning the future of the KfH.